Risky behaviors and injury severity score of the injured motorcyclist - Shahrokh Yousefzade-Chabok; Marjan Hosseinnia; Mohammad Sheikhi; Enayatollah Homaie Rad; Leila Kouchakinejad-Eramsadati; Naema Khodadadi-Hassankiadeh (Emergency Care Journal)
The aim of the present study was to investigate the relationship between self-reported motorcycling behavior and the severity of physical injuries from 2018 to 2021. This is a retrospective descriptive study. Preliminary injury data were obtained from the trauma registration system. The Short Motorcycle Behavior Questionnaire (SMRBQ) asked about the injured person's behavior during a telephone call. Data were analyzed with SPSS version 21. The Poisson regression estimation revealed a statistically significant relationship between the overall behavior of the motorcyclist and having a motorcycle license and a collision history. The incidence of serious injuries is correlated with motorcyclist behavior, age, driving purpose, driving rate during the week, motorcycle riding experience, and motorcycle driving license. Hospital outcomes had a statistically significant relationship with motorcyclist behavior, age, motor driving experience, motorcycle driving license, and collision history. By fostering a culture, educating individuals, and motivating motorcyclists in the community to obtain a permit, as well as strengthening the driving education system, traffic rules, and driver safety while riding a motorcycle, we can reduce the number of people without a license, consequently decreasing the incidence of serious injuries and improving hospital outcomes.